EFEKTIVITAS SENAM AEROBIK INTENSITAS SEDANG TERHADAP TEKANAN DARAH DAN KESEGARAN JASMANI PADA REMAJA OVERWEIGHT DI JURUSAN GIZI POLTEKKES KEMENKES SEMARANG - Winda Permatasari; Enik Sulistyowati; Yuwono Setiadi (JURNAL RISET GIZI, 2018)
Background : Overweight is one nutritional status problem with excess body fat percent, has a prolonged impact on the risk of degenerative diseases. Overweight is one of factor that triggers hypertension and affects the physical fitness of the decreasing and easily tired.Objective  : To know the effectiveness of moderate intensity aerobic exercise on blood pressure and physical fitness of overweight adolescentsatthe Nutrition Department of PoltekkesKemenkes Semarang.Methods  : This study was one of community nutrition. True-Experimental with pre and post-control group design was used. Random sampling technique was used to get 17 treatment samples and 17 control samples. The collected data contained characteristics data, anthropometric (height, weight), Systolic Blood Pressure (SBP), Dyastolic Blood Pressure (DBP), Physical fitness, energy intake and physical activity. T-tests(paired t test and independent t test) were analyzed to determine the differences between variables.Results  : After moderat intensity of aerobic exercise at 5 weeks, there was a significant different (p0,05) between treatment and control groups on physical fitness (21,84±5,25 vs 12,92±5,24 ml/kg/minutes). There were no differences (p0,05) for SBP (113.47±9,47 vs 117,17±13,11 mmHg) and DBP (80,2±11,55 vs 76,71±8,42 mmHg ) in both of group.Conclusion  : There was a difference in the increase in physical fitness of the treatment group p = 0,000 (p 0.05)